2015
DOI: 10.15255/cabeq.2014.2058
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Production and Re-use of Poly(3-hydroxybutyrate-co-3- hydroxyvalerate) and Extracellular Polysaccharide by the Archaeon Haloferax mediterranei Strain DSM 1411

Abstract: The halobacterium Haloferax mediterranei was used to study the production of two types of biopolymers: The biopolyester poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) was accumulated as intracellular granules, whereas an extracelluar polysaccharide was excreted in parallel to biopolyester synthesis.After production, microbial re-use and degradation of these polymers under different conditions were investigated to assess the requirements for handling the product-rich fermentation broth prior to the downstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 43 publications
4
19
0
Order By: Relevance
“…Simultaneous or sequential production of two biopolymers with another bio‐product has been reported previously. However, in many cases this has been based on unplanned, ad hoc observation rather than prior deliberate design . So, there is great opportunity for structured investigation, leading to potential economic advantages for bio‐industries.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Simultaneous or sequential production of two biopolymers with another bio‐product has been reported previously. However, in many cases this has been based on unplanned, ad hoc observation rather than prior deliberate design . So, there is great opportunity for structured investigation, leading to potential economic advantages for bio‐industries.…”
Section: Introductionsupporting
confidence: 93%
“…However, in many cases this has been based on unplanned, ad hoc observation rather than prior deliberate design. [15][16][17][18] there is great opportunity for structured investigation, leading to potential economic advantages for bio-industries. Simultaneous production of industrially important biopolymers is an attractive approach for a high-profit bio-refinery.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas some of these groups focused on the application of inexpensive carbon feedstocks to safe substrate costs, such as whey permeate from dairy industry [12,13,48], rice-based ethanol stillage [49], extruded rice bran [50], enzymatically extruded starch [51], crude glycerol phase [28], olive mill waste water [52], vinasse [53], etc., others clarified the enzymatic and genetic background of PHA-synthesis [54][55][56][57] and in vitro degradation [58] by this organisms. Mathematic models of PHA-production [59], and kinetic studies of PHA and by-product synthesis and degradation [60] were reported for Hfx. mediterannei.…”
Section: Discussionmentioning
confidence: 99%
“…Representatives of the latter group of microorganisms have shown a great potential for biotechnological production of, inter alia, polyhydroxyalkanoates (PHAs). For example, PHA biosynthesis by the halophilic strain Halomonas boliviensis [6] and the extremely halophilic archaeon Haloferax mediterranei [7][8][9] are described in the literature. In addition, many Bacillus species have been classified as halotolerant [10] and constitute potential candidates for PHA production.…”
Section: Introductionmentioning
confidence: 99%